Islamic Values–Based Educational Leadership in Improving Teacher Performance at Al-Hidayah Senior High School, Medan - Lubis, Namirotul Arofat; Nasution, Inom (Edumaspul: Jurnal Pendidikan, 2026)
Islamic values–based leadership of the school principal plays an important role in shaping the work culture and teacher performance at SMA Al-Hidayah Medan. Leadership practices are implemented by instilling the values of amanah (trustworthiness), honesty, justice, deliberation (musyawarah), and exemplary conduct in daily school life. These values are manifested through the habituation of religious activities, moral development programs, teacher involvement in decision-making processes, and the discipline and sense of responsibility demonstrated by the principal. Leadership that emphasizes guidance and a persuasive approach fosters harmonious working relationships between the principal and teachers and creates a religious and conducive school environment. The application of Islamic values in leadership is reflected in teachers’ performance, which shows improvements in discipline, responsibility, teaching preparedness, sincerity, and active participation in school activities. Teachers perceive their teaching duties as an amanah and a form of worship, motivating them to carry out their responsibilities with awareness and professional commitment. A work environment grounded in justice, openness, and exemplary leadership encourages teachers to work not due to pressure, but because of intrinsic motivation. The implementation of Islamic values–based leadership is supported by structured religious activities, the principal’s role modeling, strong cooperation among school members, and a religious school atmosphere. Challenges remain, particularly differences in levels of awareness, discipline, and teachers’ ability to adapt to the implemented values; however, these obstacles are addressed through continuous guidance and a humanistic approach. These findings indicate that Islamic values–based leadership contributes to improving teacher performance and building a school work culture enriched with moral and spiritual values.